The polyomavirus enhancer comprises multiple functional elements. - Mueller, C R (1988)
The polyomavirus enhancer occupies 244 base pairs within noncoding sequences between the early and late transcription units. To define more precisely the DNA sequences that make up the enhancer, we cloned it together with the viral early promoter upstream of a reporter gene, isolated mutants bearing deletions introduced in vitro in the enhancer, and measured the capacity of the various mutant genomes to express the cat gene after transient transfection into mouse 3T3 cells. Analysis of a large number of deletion mutants revealed that the enhancer is between 102 and 172 base pairs long and can be divided into at least three functional elements. Relative to the entire enhancer, individual elements possessed little or no enhancer activity. However, pairs of elements enhanced transcription to levels much higher than the sum of individual elements approximating the activity of the complete enhancer. These findings support the view that the polyomavirus enhancer is composed of multiple sequence elements that function combinatorily and imply that a measure of cooperation exists in the interaction between cellular protein factors bound to their cognate sites in the enhancer and the transcriptional machinery of the cell.